2008
DOI: 10.1242/jcs.022418
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and lateral mobility of DC-SIGN on immature dendritic cells–implications for pathogen uptake

Abstract: The receptor C-type lectin DC-SIGN (CD209) is expressed by immature dendritic cells, functioning as an antigen capture receptor and cell adhesion molecule. Various microbes, including HIV-1, can exploit binding to DC-SIGN to gain entry to dendritic cells. DC-SIGN forms discrete nanoscale clusters on immature dendritic cells that are thought to be important for viral binding. We confirmed that these DC-SIGN clusters also exist both in live dendritic cells and in cell lines that ectopically express DC-SIGN. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
68
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 43 publications
(46 reference statements)
8
68
0
Order By: Relevance
“…Movements over such short distance (several micrometers) might be achieved by normal diffusion. Internalization in the sites around the nucleus can be achieved by the direct binding of viral particles at these sites (our unpublished data) or by viral surfing on the cell membrane to these sites (34). Our studies do not exclude the possibility that AAV2 particles may reach the nucleus through a much slower process by exploiting actin filaments or intermediate filaments (35,43).…”
Section: Discussionmentioning
confidence: 79%
“…Movements over such short distance (several micrometers) might be achieved by normal diffusion. Internalization in the sites around the nucleus can be achieved by the direct binding of viral particles at these sites (our unpublished data) or by viral surfing on the cell membrane to these sites (34). Our studies do not exclude the possibility that AAV2 particles may reach the nucleus through a much slower process by exploiting actin filaments or intermediate filaments (35,43).…”
Section: Discussionmentioning
confidence: 79%
“…Recently, we demonstrated that on the plasma membrane of DC, DC-SIGN is organized in nanoclusters, some of which colocalize with lipid rafts, that specifically confer to the receptor its capacity of binding and internalizing viruses as well as Ag conjugated to fluorescent nanoparticles [9,10]. These findings were substantiated by a biophysical study by Neumann et al, who showed that these nanoclusters are enriched near the leading edge of living DC, but are preferentially endocytosed at lamellar sites posterior to the leading edge, suggesting a directed mobility of DC-SIGN from areas of concentration at the front to rearward sites of internalization [11].…”
Section: Introductionmentioning
confidence: 84%
“…These domains have interesting biophysical properties, such as a lack of exchange of receptor with the surrounding membrane and nearly complete segregation of DC-SIGN and CD206 nanodomains in resting DC membranes [68][70]. Recently, we have observed that nanoscale organization of CTLs in fungal contacts is altered relative to non-contact membrane in favor of less individual nanodomain structure and more longer-range nanostructure, consistent with close packing of domains (unpublished data, AKN).…”
Section: Discussionmentioning
confidence: 61%